Morfofonemik Bahasa Talaud - Lalira, James (Universitas Sam Ratulangi, 2013)
The research of Talaud morphophonemics is based on structural linguistic study. There are two sub-disciplines of structural linguistics that contributes in developing and analyzing morphophonemics research, which is morphology and phonology. This research is motivated by the renewal of Talaud language structure and aims to describe the process, formulate rules and identify types of assimilation morphophonemics in Talaud language. This research uses descriptive method. Source of the data is taken from the informants who were native speaker of Talaud language. The data collecting techniques was in terms of observing, oral interactive and note taking. While, technique of analysis data started by describing phonemes, then describing morphemes in the form of free and bound morphemeBased on the result of research, three morphophonemics processes have been found namely processes of change, addition, and deletion of phoneme. From the three processes, phonemic changing process always indicates the sound alignment pattern examined in terms of phonemic homorganic form. For example, the replacement ofÂ Â Â / N / to /m/ /n/, /á¿ƒ/, when matched with the word stem beginning with phonemes /b, p/ /d, t/ /h/, respectively. This research has also successfully identified the type of morphophonemics assimilation. The morphophonemic assimilation of Talaud language can be viewed in terms of assimilation types based on where the process occurs and the nature of assimilation. At least there are three types of assimilation based on the place of occurrence, namely progressive, regressive and reciprocal assimilation. On the other hand, the assimilation based on the nature has two types, namely total and partial assimilation. This process of morphophonemics and particularly assimilation is then described in the chart showing the rules of morphophonemics so that, the language phenomena that occur is easily visible. Key words: Talaud language morphophonemics, processes, rules.